Effects of drying pretreatment and particle size adjustment on the composting process of discarded flue-cured tobacco leaves. Issue 5 (May 2017) - Zhao, Gui-Hong; Yu, Yan-Ling; Zhou, Xiang-Tong; Lu, Bin-Yu; Li, Zi-Mu; Feng, Yu-Jie
The main characteristic of discarded flue-cured tobacco leaves is their high nicotine content. Aerobic composting is an effective method to decrease the nicotine level in tobacco leaves and stabilize tobacco wastes. However, high levels of nicotine in discarded flue-cured tobacco leaves complicate tobacco waste composting. This work proposes a drying pretreatment process to reduce the nicotine content in discarded flue-cured tobacco leaves and thus enhance its carbon-to-nitrogen ratio to a suitable level for composting. The effect of another pretreatment method, particle size adjustment, on composting efficiency was also tested in this work. The results indicated that the air-dried (nicotine content: 1.35%) and relatively long discarded flue-cured tobacco leaves (25 mm) had a higher composting efficiency than damp (nicotine content: 1.57%) and short discarded flue-cured tobacco leaves (15 mm). When dry/25 mm discarded flue-cured tobacco leaves mixed with tobacco stems in an 8:2 ratio was composted at a temperature above 55 °C for 9 days, the nicotine content dropped from 1.29% to 0.28%. Since the discarded flue-cured tobacco leaves was successfully composted to a fertile and harmless material, the germination index values increased to 85.2%. The drying pretreatment and particle size adjustment offered ideal physical and chemical conditions to support microbial growth and bioactivity during the composting process, resulting in efficient conversion of discarded flue-cured tobacco leaves into a high quality and mature compost.